Development of the philometrids Philometra overstreeti and philometroides paralichthydis in the experimentally infected copepod Oithona colcarva - Bryan, Timothy P; Tsoi, Lam C; de Buron, Isaure (Folia parasitologica, 2008)
Philometra overstreeti Moravec et de Buron, 2006 and Philomnetroides paralichthydis Moravec et de Buron, 2006 are common parasites of the southern flounder, Paralichthys lethostigma Jordan et Gilbert. Because the life cycles of these parasites are unknown, our goal was to assess whether species of copepod commonly found in our estuaries could serve as intermediate hosts for these philometrids. Individuals of five species of copepods were collected and exposed to L1 larvae of each philometrid species. The cyclopoid Oithlona colcarva Bowman was the only species to become successfully infected. Successive moulting of philometrid larvae in the haemocoel of the copepods was studied using transmission electron microscopy. At 23 degrees C the moult from L1 to L2 was observed for both species as early as 24 h post exposure to L1 larvae. The moult from L2 to L3 was initiated within 2 days post exposure and completed by 6-7 days post exposure. Some parasite-induced tissue damage occurred in the copepod but no cellular response against larval philometrids was observed.
Keywords: Flounder; Nematoda; časové faktory; zvířata; hlístice; Animals; platýs; larva; interakce hostitele a parazita; stadia vývoje; Larva; Life Cycle Stages; Host-Parasite Interactions; Copepoda; Time Factors